Rectal cancer: Dynamic contrast‐enhanced MRI correlates with lymph node status and epidermal growth factor receptor expression. Issue 6 (11th October 2013) - Lollert, André; Junginger, Theodor; Schimanski, Carl Christoph; Biesterfeld, Stefan; Gockel, Ines; Düber, Christoph; Oberholzer, Katja
<x xml:space="preserve">Abstract</x> Purpose To evaluate correlations between dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) and clinicopathologic data as well as immunostaining of the markers of angiogenesis epidermal growth factor receptor (EGFR) and CXC‐motif chemokine receptor 4 (CXCR4) in patients with rectal cancer. Materials and Methods Presurgical DCE‐MRI was performed in 41 patients according to a standardized protocol. Two quantitative parameters (k21, A) were derived from a pharmacokinetic two‐compartment model, and one semiquantitative parameter (TTP) was assessed. Standardized surgery and histopathologic examinations were performed in all patients. Immunostaining for EGFR and CXCR4 was performed and evaluated with a standardized scoring system. Results DCE‐MRI parameter A correlated significantly with the N category (P = 0.048) and k21 with the occurrence of synchronous and metachronous distant metastases (P = 0.029). A trend was shown toward a correlation between k21 and EGFR expression (P = 0.107). A significant correlation was found between DCE‐MRI parameter TTP and the expression of EGFR (P = 0.044). DCE‐MRI data did not correlate with CXCR4 expression. Conclusion DCE‐MRI is a noninvasive method which can characterize microcirculation in rectal cancer and correlates with EGFR expression. Given the relationship between the dynamic parameters and the clinicopathologic data, DCE‐MRI data may constitute a prognostic indicator for lymph node and distant metastases in patients with rectal cancer. J. Magn. Reson. Imaging 2014;39:1436–1442. © 2013 Wiley Periodicals, Inc.